Access to advanced cancer care services in the West Bank-occupied Palestinian territory - Mitwalli, Suzan; Hammoudeh, Weeam; Giacaman, Rita; Harding, Richard (Frontiers in Oncology, 2023)
Introduction Universal Health Coverage (UHC) identifies the provision of palliative care for people with advanced disease as an essential health service. Palliative care is also stipulated as a human right under existing covenants. Oncology services provided by the Palestinian Authority under Israeli military occupation are limited to surgery and chemotherapy treatment. Our study aimed to describe the experiences of patients with advanced-stage cancer in the West Bank in accessing oncology services and meeting their health care needs. Methodology We conducted a qualitative study among adult patients diagnosed with advanced lung, colon, or breast cancer in three Palestinian governmental hospitals, and with oncologists. Thematic analysis was conducted on the verbatim interview transcripts. Results The sample consisted of 22 Palestinian patients (10 men and 12 women) and 3 practicing oncologists. The findings reveal that cancer care is fragmented, with limited access to the services needed. Patients face referral delays in accessing treatment which worsen their health condition in some cases. Some patients reported difficulties in getting Israeli permits to access radiotherapy treatment in East-Jerusalem, and others experienced interruptions of their chemotherapy treatment sessions due to the unavailability of chemotherapy medications caused by Israeli-side delays. Other reported problems were related to the Palestinian health system and service delivery and quality, including fragmentation of services, infrastructure issues, and unavailability of medications. Advanced diagnostic services and palliative care are almost absent at Palestinian governmental hospitals, and patients need to seek these services in the private sector. Conclusion The data demonstrate specific access restrictions to cancer care in the West Bank due to Israeli military occupation of Palestinian land. This affects all stages of the care pathway, from restricted diagnosis services, to limited treatment and then poor availability of palliative care. Cancer patients will continue to suffer if the root causes of these structural constraints are not addressed.